Numerical transient modeling of a flat plate solar collector - Aouf Abdulrahman Al-Tabbakh (Results in Engineering, 2022)
The present study deals with numerical simulation of a typical flat plate solar collector. The transient two-dimensional governing differential equations of absorber plate, working fluid and glass cover were formulated to describe the thermal problem of the collector. The governing differential equations were solved numerically using Finite Differences Method and the transient problem was formulated using implicit scheme which gives a stable solution for any grid size and time step. The two-dimensional temperature distribution in absorber plate was achieved at 2211 nodes at every 10 s of the simulation period that extended for 1800 s. The variation of fluid exit temperature and glass cover temperature were also estimated. The estimation of top heat loss coefficient and collector efficiency becomes possible using the temperature distributions of absorber plate and working fluid along with cover temperature. The variations of mean plate temperature, fluid exit temperature, cover temperature, top heat loss coefficient and collector efficiency were drawn during the simulation period. Temperature distribution contours were also drawn at selected time intervals and irradiance values. It was concluded that the top heat loss coefficient of the solar collector is a strong function of the irradiance and working fluid mass flow rate. Increasing the value of mass flow rate shortened the transient period of the solar collector and rendered the transient curves of the collector parameters more flat. The study can be useful for further understanding the complex transient two-dimensional thermal problem occurring in flat plate solar collectors.